Risk assessment framework and criteria for major accidental release to the environment in Malaysia - 445491 M. Wijayanuddin Ali; National Conference & Exhibition on Occupational Safety and Health (5th : 2002 : Selangor) (Skudai : Universiti Teknologi Malaysia)
42